The African Queen [videorecording (DVD)] - Huston, John, 1906-1987; Bogart, Humphrey, 1899-1957; Hepburn, Katharine, 1907-2003; Morley, Robert; Bikel, Theodore; Bull, Peter, 1912-1984; Forester, C. S. (Cecil Scott), 1899-1966 (Paramount Home Entertainment, 2010)
At the start of World War I, German imperial troops burn down a mission in Africa. The mission's reverend was so overtaken with disappointment that he passes away. Shortly after his well-educated, snooty sister Rose buries her brother, she must leave on the only available transport, the 'African Queen' steamboat. The boat is manned by the ill-mannered bachelor, Charlie. Together they embark on a long difficult journey, without any comfort. Rose grows determined to assist in the British war effort and presses Charlie until he finally agrees and together they steam up the Ulana encountering an enemy fort, raging rapids, bloodthirsty parasites and endlessly branching steam which always seem to lead them to what appear to be impenetrable swamps. Despite their opposing personalities, the two grow closer to each other and ultimately carry out their plan to take out a German warship.